Penatalaksanaan Holistik Pada Wanita Usia 21 Tahun dengan Asma Persisten Ringan Melalui Pendekatan Kedokteran Keluarga - Rika Partika; Azelia Nusadewiarti (CV. Jasa Sukses Abadi, 2023)
Indonesia is ranked 19th in the world regarding deaths due to asthma. Asthma is a heterogeneous disease characterized by chronic airway inflammation. Asthma is a reversible obstructive disorders which is requires control to improve the patient's quality of life. Holistic management through a family medicine approach is expected to be able to assist patients in identifying, controlling precipitating factors and preventing individuals with predisposition to asthma from developing asthma and preventing asthma patients from experiencing asthma attacks. In this study, primary data were obtained from autoanamnesis, physical examination and home visits. Secondary data was obtained from the patient's medical record. Patient Ms. C, 21 years old, has a main complaint of shortness of breath accompanied by a feeling of heaviness in the chest, coughing, and